(untitled) (Experimental biology, 2023)
The composition of zooplankton of freshwater lakes of the Alakol system in the spring-summer period of 2021 was represented by 33 varieties. In oz. Sasykkol the number of taxa did not change by season and amounted to 14 names. In oz. Koshkarkol their number decreased from spring to summer - from 11 to 6. The biomass of zooplankton of the lake. Sasykkol increased from 1220.17 to 1973.39 mg/m3. In May, the south-eastern region was more productive -1607.01 mg/m3, and in summer - the north-eastern region - 2575.24 mg/m3. The level of zooplankton trophicity in the lake. Sasykkol for the spring-summer period corresponded to a moderate class. In oz. Koshkarkol biomass index ranged from 940.12 to 2856.54 mg/m3. On average in the lake’s water area, zooplankton corresponded to a "moderate" trophic class. Relative to 2020, the weight of zooplankton biomass of the lake. Sasykkol increased by 73%, in summer – by 69%. In May, compared with last year’s data, the biomass of the lake. Kosh-karkol increased by 65%, and in August – by 32%. During the observation period since 2017, the productivity of zooplankton of the lake. Sasykkol and Koshkarkol in the spring-summer period corresponded to a moderate class. The research is funded by the Ministry of Ecology, Geology and Natural Resources of the Republic of Kazakhstan (Grant no. BR10264205).